Deoxynucleoside Kinases of Bacillus megaterium KM - Wachsman, J. T. (1971)
Dialyzed extracts of Bacillus megaterium KM contain thymidine, deoxyadenosine, and deoxyguanosine kinase activities. Thymidine kinase activity is best with deoxyadenosine triphosphate or deoxyguanosine triphosphate (dGTP) as the phosphoryl donor, whereas the best deoxyadenosine kinase activity is obtained with dGTP or adenosine triphosphate. Deoxyguanosine kinase activity functions optimally with deoxycytidine triphosphate as the donor. Although the thymidine kinase activity of crude extracts does not have a demonstrable divalent cation requirement, the addition of Mg(2+) or Mn(2+) is necessary for the formation of thymidine di- and triphosphates. The synthesis of thymidine kinase appears to be partially derepressed by thymine starvation. Incubation of extracts with deoxyadenosine and dGTP results in the substantial accumulation of deoxyadenosine di- and triphosphates. Extracts deaminate deoxycytidine to deoxyuridine, presumably as a consequence of the action of deoxycytidine deaminase, and then convert deoxyuridine to deoxyuridylic acid. B. megaterium extracts do not contain any detectable deoxycytidine kinase activity.